P PENGARUH AUDIT FORENSIK TERHADAP PENCEGAHAN DAN DETEKSI KECURANGAN - Farman, Safril; ., Wahyuni; Saputri, Nabila; ., Yusriani (AKRUAL : Jurnal Akuntansi dan Keuangan, 2025)
Fraud in financial statements poses a serious threat to the integrity of financial information and organizational stability. Forensic audit emerges as an investigative auditing approach specifically aimed at uncovering, preventing, and proving fraudulent acts in a systematic manner. This study aims to analyze the influence of forensic audit on the prevention and detection of fraud in financial statements through a literature review approach. Data were collected from various secondary sources such as academic journals, textbooks, and relevant institutional reports. The findings indicate that forensic audit plays a crucial role in strengthening internal control systems, identifying suspicious transaction patterns, and preventing potential fraud through enhanced monitoring and compliance. Additionally, forensic audit proves effective in detecting and uncovering fraudulent activities by applying in-depth data analysis and investigative techniques. However, the study is limited by its reliance on secondary data and the absence of primary empirical validation, which constrains the generalizability of the findings. This research recommends enhancing the capacity of forensic auditors and implementing forensic audits more broadly as part of effective corporate governance practices.